The impact of preoperative salivary urea and superoxide dismutase activities on postoperative pain after surgical removal of mandibular third molars - Nino Grgić; Marko Tarle; Ante Perić; Slavica Potočki; Daria Pašalić; Berislav Perić (Acta Clinica Croatica)
The most frequent surgical procedure in oral surgery is extraction of mandibular third molars, which could be associated with postoperative complications such as pain, swelling, and trismus. We aimed to investigate the association of salivary urea and antioxidative enzyme activities with the intensity of postoperative pain after wisdom tooth extraction. This cross-sectional prospective study included 66 subjects (median age 25, range 17-47 years). Salivary urea and superoxide dismutase (SOD) were determined by enzymatic colorimetric tests. The questionnaire for study participants included demographic and history data, as well as data on personal experience of pain in grade 0-10 according to the visual analog scale (VAS). Grading 1-3 was considered as low (VAS-1), 4-6 mild (VAS-2) and 7-10 as severe pain (VAS-3). Moderate positive correlation was recorded between urea concentration and SOD activity in saliva (r=0.46). Moderate negative correlations were found between urea salivary concentration and VAS grading value reported after 12 hours (r=0.51). The concentrations of urea significantly differed among the three VAS categories (p<0.001), whereas salivary SOD activities did not differ among the categories. Preoperative salivary urea concentration and SOD activity might be associated with postsurgical pain after surgical removal of mandibular third molars.